2006
DOI: 10.1172/jci17891
|View full text |Cite
|
Sign up to set email alerts
|

Role of different pathways of the complement cascade in experimental bullous pemphigoid

Abstract: Bullous pemphigoid (BP) is an autoimmune subepidermal blistering disease associated with autoantibodies directed against the hemidesmosomal proteins BP180 and BP230 and inflammation. Passive transfer of antibodies to the murine BP180 (mBP180) induces a skin disease that closely resembles human BP. In the present study, we defined the roles of the different complement activation pathways in this model system. Mice deficient in the alternative pathway component factor B (Fb) and injected with pathogenic anti-mBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 58 publications
1
90
0
1
Order By: Relevance
“…The rationale of our study to probe the effects of 17-DMAG on BP IgG-induced IL-6 and IL-8 production by HaCaT cells was mainly based on three documented findings: (i) both inflammatory cytokines play a key role in the pathophysiology of BP (Schmidt et al 1996a, b;Liu et al 1997;Inaoki and Takehara 1998;Schmidt et al 2000;Chen et al 2001;Schmidt et al 2001;Nelson et al 2006;Messingham et al 2011), (ii) the extensive list of Hsp90 client proteins includes many proinflammatory molecules (Salminen et al 2008;Taipale et al 2010;Henderson and Kaiser 2013), and (iii) recent evidence suggests that Hsp90 represents a novel treatment target in autoimmune bullous diseases (Kasperkiewicz et al 2011;Tukaj et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale of our study to probe the effects of 17-DMAG on BP IgG-induced IL-6 and IL-8 production by HaCaT cells was mainly based on three documented findings: (i) both inflammatory cytokines play a key role in the pathophysiology of BP (Schmidt et al 1996a, b;Liu et al 1997;Inaoki and Takehara 1998;Schmidt et al 2000;Chen et al 2001;Schmidt et al 2001;Nelson et al 2006;Messingham et al 2011), (ii) the extensive list of Hsp90 client proteins includes many proinflammatory molecules (Salminen et al 2008;Taipale et al 2010;Henderson and Kaiser 2013), and (iii) recent evidence suggests that Hsp90 represents a novel treatment target in autoimmune bullous diseases (Kasperkiewicz et al 2011;Tukaj et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise sequence of these events is largely unknown, it has been proposed that one of the first steps leading to blister formation in BP comprise the binding of autoantibodies to BP180, thereby initiating Fc receptor-independent events leading to the release of interleukin 6 (IL-6) and IL-8 from basal keratinocytes (Schmidt et al 2000(Schmidt et al , 2001Messingham et al 2011). IL-8 is a potent chemoattractant for pathophysiologically relevant leukocyte effector cells and together with IL-6 known to be elevated in sera and blister fluids of BP patients and critical for blister formation in mouse models (Schmidt et al 1996a, b;Liu et al 1997;Inaoki and Takehara 1998;Chen et al 2001;Nelson et al 2006;Kobayashi 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Level of Skin C5a-We previously reported that the classical pathway of complement activation is critical to the pathogenesis of experimental BP in mice (18). Wild-type mice (C4 ϩ/ϩ ) and mice deficient in the alternative pathway component factor B (Fb Ϫ/Ϫ ) developed subepidermal blisters following injection with pathogenic anti-murine BP180 IgG; however, mice deficient in the classical pathway component C4 (C4 Ϫ/Ϫ ) were resistant to blister formation ( Fig.…”
Section: Mice Lacking the Classical Pathway Of The Complement System mentioning
confidence: 98%
“…The complement system and MC activation are indispensable to the pathogenesis of experimental BP (18,40). Having demonstrated that p38 MAPK activation is also required for disease development, we next investigated the links between complement, MCs, and p38 MAPK.…”
Section: C5ar-mediated P38 Mapk Activation Depends On Mcs-mentioning
confidence: 99%
See 1 more Smart Citation